YOUTH CULTURE DAN GAYA BUSANA: HIPER-REALITAS PEKERJA MUDA PEREMPUAN TERHADAP PRODUK FASHION BERMEREK DI JAKARTA - Ernungtyas, Niken Febrina; Puspita, Ratih; Suryaningsih, Sri Indah; Amelia, Yesi Rizki; Lamini, Lamini; Hendarrita, Yana (Universitas Merdeka Malang, 2016)
Abstract Fashion has practically become an integral part of anybodyâ€™s life style on day- to-day basis. Nowadays, it is no longer a mere cloth covering her/his body to protect it from head and cold. Furthermore, it has transformed to be a tool of self-expression, self-image and self- identity of the person putting it on. By fashion here to means a valuable imported branded cloth. Against this backdrop, the research attempts to explicate why the informant (Jakartan young female professional) do so at the expense of meeting their daily basic neeeds. What values (power) they want to obtain by wearing those branded clothes.This qualitative study also tries to explore how they make sense of putting on those imported clothes. After collecting data through observation and interview, the study found that they did so in return for exchange value; psedou power which fall into three categories; superior, trendsetters and dominator. They were captuted by what it is as hyper-reality. Added to that, they did so in order to meet social values from their close social circle. Those values are such as a praise from others, self-confidence, self-image, and self-satisfaction. Keywords: Fashion, lifestyle, hyper-reality, pseudo-powerDOI :Â https://doi.org/10.26905/nomosleca.v2i1.379